2022
DOI: 10.3389/fpubh.2022.953363
|View full text |Cite
|
Sign up to set email alerts
|

The effect of horticultural therapy on depressive symptoms among the elderly: A systematic review and meta-analysis

Abstract: ObjectiveThis systematic review and meta-analysis aimed to assess the effectiveness of horticultural therapy on depressive symptoms in the elderly and determine the potential moderators of the intervention effect.MethodsIn early June 2022, randomized controlled trials and Quasi-experimental studies were searched on Web of Science, PsycINFO, CINAHL, EMBASE, Medline, PubMed, CNKI, WANFANG DATA, and CQVIP. Three independent authors proposed the following inclusion criterion for this study: the elderly with applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 76 publications
1
16
0
Order By: Relevance
“…In the study conducted by Kim et al with participants composed of middle-aged women, it was discerned that, among interventions, the horticultural therapy was of signi cance to participants' depression, anxiety, and self-de nition, and in this respect, the experimental group exhibited more signi cant developments than the control group [50]. In the metaanalysis performed by Zhang et al to identify the effect of horticultural therapy on depressive symptoms, it was indicated that horticultural therapy had a positive effect on the consequences of depressive symptoms [51]. In the study by Noone et al and in the study by Domenceh-Abella et al, it was stated that horticultural activities that were performed collectively promoted community integration by developing social attachment and were a tool for the alleviation of individuals' depressive symptoms, which stemmed from loneliness and the lack of social interaction [52][53].…”
Section: Discussionmentioning
confidence: 99%
“…In the study conducted by Kim et al with participants composed of middle-aged women, it was discerned that, among interventions, the horticultural therapy was of signi cance to participants' depression, anxiety, and self-de nition, and in this respect, the experimental group exhibited more signi cant developments than the control group [50]. In the metaanalysis performed by Zhang et al to identify the effect of horticultural therapy on depressive symptoms, it was indicated that horticultural therapy had a positive effect on the consequences of depressive symptoms [51]. In the study by Noone et al and in the study by Domenceh-Abella et al, it was stated that horticultural activities that were performed collectively promoted community integration by developing social attachment and were a tool for the alleviation of individuals' depressive symptoms, which stemmed from loneliness and the lack of social interaction [52][53].…”
Section: Discussionmentioning
confidence: 99%
“…impact on well-being and mental health Kamioka et al (2014) [ 21 ] 4 ( N = 248) Japan Interventional Horticultural therapy Well-being, mental health, quality of life + impact on mental health and behaviour Kondo et al (2018) [ 22 ] 43 ( N = 1915) USA Interventional Gardening Mental health + impact on cortisol; ? impact for mood, anxiety Lin et al (2021) [ 23 ] 10 ( N = 884) China Interventional Horticultural therapy Well-being, mental health, quality of life + impact on mental health, quality of life, and well-being Lin et al (2022) [ 24 ] 16 ( N = 960) UK Interventional Horticultural therapy Well-being + impact on well-being Spano et al (2020) [ 25 ] 7 ( N = 1699) Italy Interventional Gardening; horticultural therapy Well-being + impact on well-being Tu and Chiu (2020) [ 26 ] 10 ( N = 340) Taiwan Interventional Horticultural therapy Mental health + impact on mental health (cognition) Zhang et al (2022) [ 27 ] 13 ...…”
Section: Resultsmentioning
confidence: 99%
“…The review by Coventry et al [ 9 ] reported a beneficial role of gardening in reducing symptoms of anxiety and negative effects in people with several mental illnesses. Horticultural therapy was also found to be effective in reducing depressive symptoms and improving cognitive performance [ 10 , 21 , 26 , 27 , 33 , 40 , 42 , 50 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…This finding makes TSPO an even more interesting target for a noninvasive diagnosis of endometriosis, as the test could be performed at any time of the menstrual cycle and specially during hormonal endometriosis treatment. This is an ideal situation, considering that stopping the treatment causes pain and decreases women's quality of life (Szyplowska et al, 2023).…”
Section: Discussionmentioning
confidence: 99%